2009
DOI: 10.1182/blood-2009-01-199919
|View full text |Cite
|
Sign up to set email alerts
|

FcγRI ligation leads to a complex with BLT1 in lipid rafts that enhances rat lung macrophage antimicrobial functions

Abstract: IntroductionMacrophages play a central role in antimicrobial immunity via their capacities for recognition, phagocytosis, and killing of opsonized and nonopsonized microbes. Nowhere are these functions more vigorously tested than in the lung, which comprises the largest internal interface with the outside environment and which is continuously exposed to microbes delivered via inhalation or oropharyngeal aspiration. 1 Particles opsonized by immunoglobulin (Ig)G antibodies bind to receptors recognizing the Fc po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…This report provides evidence that 3-mm IgG-opsonized particles activate the Ral GTPases and that these proteins can modulate phagocytic efficiency. Activation of the Ral proteins is mediated, at least in part, by the engagement of FcgR, although simultaneous cross-activation of other phagocytosis receptors (23,24) cannot be excluded. However, our findings are in line with recent observations indicating that the GTPase Rap1 and Ral guanine-dissociation stimulator, a guanosine exchange factor that can activate Ral proteins, participate in FcgR-dependent phagocytosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…This report provides evidence that 3-mm IgG-opsonized particles activate the Ral GTPases and that these proteins can modulate phagocytic efficiency. Activation of the Ral proteins is mediated, at least in part, by the engagement of FcgR, although simultaneous cross-activation of other phagocytosis receptors (23,24) cannot be excluded. However, our findings are in line with recent observations indicating that the GTPase Rap1 and Ral guanine-dissociation stimulator, a guanosine exchange factor that can activate Ral proteins, participate in FcgR-dependent phagocytosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages adhered on coverslips were stimulated with LPS or poly(I:C) for 24 hours (42). In other experiments, leukocytes were obtained from the lung lavage fluid of mice infected with S. pneumoniae and subsequently treated with aerosolized vehicle or LTB4 24 hours after infection.…”
Section: Animals 8-week-old Female 5-lomentioning
confidence: 99%
“…However, although LTB 4 has been shown to activate macrophage phagocytosis, details of the intracellular mechanism of LTB 4 -dependent activation of phagocytosis remain to be elucidated. Recently, Serezani et al (17) showed that Fc␥RI engagement results in tyrosine phosphorylation of BLT1 by Src and subsequent formation of a molecular complex of Fc␥RI and BLT1 within lipid rafts that drives phagocytic functions in rat alveolar macrophages. However, it remains to be determined whether there is direct cross-talk between LTB 4 -BLT1 and IgG-Fc␥Rs signaling pathways.…”
mentioning
confidence: 99%